Sitotoksisitas Minyak Mesoyi (Cryptocarya massoy) terhadap Sel Vero (Cytotoxicity of Mesoyi Oil (Cryptocarya massoy) on Vero Cell Lines) - Bawon Triatmoko; Triana Hertiani; Agustinus Yuswanto (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Mesoyi oil distilled from the bark of Cryptocarya massoy have been used for traditional treatment of various ethnicities. However, its safety use has not been widely studied. This study aimed to investigate the cytotoxicity of mesoyi oil on vero cells in vitro. The Inhibitory concentration 50% (IC50) of mesoyi oil is evaluated using MTT assay. The results indicated that the mesoyi oil exhibited cytotoxic effects on vero cells with IC50 value of 97.4 μg//mL. This call for further studies to evaluate the cytotoxic activity in vivo. Keywords: cytotoxicity, essential oil, cryptocarya massoy, vero cell